Implementasi Pelatihan Mesin Pengupas Kelapa Untuk Peningkatan Usaha Air Kelapa Muda Di Petukangan Utara, Jakarta Selatan - Yamin Lubis, M. Sobron; Wijaya, Franky; Hasim, Lim Bryant; Wardani, Ni Luh Putu Agung Chandra Kusuma; Sadikin, Michael; Ariyanti, Silvi (CV. IRA PUBLISHING, 2025)
Young coconut water is a natural beverage favored for its refreshing taste and health benefits. The vitamins in its soft flesh also help maintain physical fitness. Demand increases during the dry season and the fasting month. One entrepreneur, Mr. Rakhwadi, based on Jl. Mukhtar Raya, South Jakarta, has been running this business for three years. Consumer preferences vary, with some preferring a natural taste without added sugar or ice. The peeling process is generally still manual, requiring considerable effort and time. This community service activity aims to provide training on using a coconut peeling machine to speed up the process, reduce labor, and produce more uniform results. The training involved business partners and four mechanical engineering students. The results showed that peeling time decreased from ±90 seconds to ±20 seconds, the coconut shapes were more consistent, labor use was more efficient, and production increased. The use of the peeling machine has strong potential to improve both efficiency and product value.